2019
DOI: 10.1177/0361198119845885
|View full text |Cite
|
Sign up to set email alerts
|

Platoon of SAE Level-2 Automated Vehicles on Public Roads: Setup, Traffic Interactions, and Stability

Abstract: An increasing amount of vehicles are equipped with driver assistance systems; many of the vehicles currently on the market can be optionally equipped with adaptive cruise control and lane centering systems. Using both systems at the same time brings the vehicle to SAE level-2 automation . This means a driver does not need to perform longitudinal and lateral operational driving, although the driver should be ready to intervene at any time. While this can provide comfort, the interaction between vehicles operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…With the estimated parameters from each of the methods, we check the string stability of the vehicle under ACC control. Like all previous studies considering commercial ACC systems [9,10,15,21], we find that the calibrated model of the vehicle tested in this work is neither L 2 or L ∞ strict string stable. The results are consistent across the different calibration methods, as summarized in Table 4.…”
Section: Parameter Estimation Results On a 2019 Acc Vehiclesupporting
confidence: 71%
See 3 more Smart Citations
“…With the estimated parameters from each of the methods, we check the string stability of the vehicle under ACC control. Like all previous studies considering commercial ACC systems [9,10,15,21], we find that the calibrated model of the vehicle tested in this work is neither L 2 or L ∞ strict string stable. The results are consistent across the different calibration methods, as summarized in Table 4.…”
Section: Parameter Estimation Results On a 2019 Acc Vehiclesupporting
confidence: 71%
“…Recently, as the vehicle systems have transitioned from research to practical deployments on commercial vehicles, the traffic modeling community is now in need of good models for how these vehicles behave in practice. Surprisingly, all commercial systems that have been tested [9,15,18,19,21,33] are shown to be string unstable and with varying performance characteristics. Being able to characterize the behavior of the ACC system in real time has implications for traffic management, where an emerging area of research [6,9,38,41,44] aims to dampen phantom traffic jams caused by string unstable driving behavior [34].…”
Section: Motivation and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…The instability can be solved through V2V communication, which is the key to have the highest possible gain from AVs as stated by Shladover (57). Stability is also studied in the work of Knoop et al (59), which describes an experiment with seven SAE level-2 vehicles driven as a platoon for a trip of almost 500 km. The traffic dynamics in this experiment showed that the platoon becomes unstable when all vehicles have ACC activated.…”
Section: Relevant Workmentioning
confidence: 99%